DEVELOPING AN ARCHIVAL DESCRIPTION FRAMEWORK FOR ORAL HISTORY TRANSCRIPTS AND MANUSCRIPTS BASED ON REQUIREMENTS OF ISAAR-CPF, ISAD-G AND ORAL HISTORY MANUAL (OHM) - Jannatul Iza Ahmad Kamal; Alwi Mohd Yunus; Nik Azliza Nik Ariffin (Journal of Islamic, Social, Economics and Development, 2023)
The purpose of this study is to explore the use of the International Standard Archival Authority Record for Corporate Bodies, Persons, and Families 2nd edition (ISAAR-CPF), International Standard of Archival Description (General) (ISAD-G), and the Oral History Manual (OHM) in the development of archival authority records descriptive sheet on oral history transcripts. The main effort is to provide standard descriptions and mechanisms of oral history collections associated with the creation and maintenance of primary sources. Thousands of manuscripts are kept in the Oral History Lab of the School of Information Science (SIS), UiTM, Puncak Perdana Campus, covering a wide range of subjects such as cultural, military, education, arts, political, social, literature, and many others. Currently, there is no specific approach or mechanism to describe those oral history transcripts. This case study outlines the need for the application of essential elements of descriptions of archival materials and authority records that focus on the personal entities with descriptive elements of identity, description, relationship, control area, and relating the entities to archival materials and other sources. The findings from this study contribute to the proper and practical application of archival descriptions for oral history transcripts available for user access and search, location retrieval, and authority description in that context. A necessary framework is suitable for managing archival materials in the context of oral history manuscripts embedding ISAAR-CPF, ISAD-G, and OHM would be suggested for use. It tends to propose its application in the developmental context of archival authority records for oral history transcripts at the Oral History Lab of SIS and hence practically applied for access and storage while maintaining context to its specific audio and video recording and processes.